-8
Пошаговое объяснение:
4(15x-4y)-2(12y-5x)=
раскроем скобки и приведём подобные:
=60х-16у-24у+10х=70х-40у=
Представим в таком виде:
=-10(4у-7х)
А так как 4y-7x=0,8⇒-10(4у-7х)=-10*0,8=-8
Если 4y-7x=0,8 |×10/2
20y-35x=4
4(15x-4y)-2(12y-5x)=2(30x-8y-12y+5x)=2(35x-20y)=2·(-4)=-8
-8
Пошаговое объяснение:
4(15x-4y)-2(12y-5x)=
раскроем скобки и приведём подобные:
=60х-16у-24у+10х=70х-40у=
Представим в таком виде:
=-10(4у-7х)
А так как 4y-7x=0,8⇒-10(4у-7х)=-10*0,8=-8
-8
Пошаговое объяснение:
Если 4y-7x=0,8 |×10/2
20y-35x=4
4(15x-4y)-2(12y-5x)=2(30x-8y-12y+5x)=2(35x-20y)=2·(-4)=-8